Self-Aligned Multilayer Dielectric “DummyGate” Technology for L–, S– and X–Band GaAsMMICs Fabrication; Micro/Nanosystems Technologies, MNST'2010 - Anishchenko E. V. Ekaterina; Arykov V. S. Vadim; Gavrilova A. M. Anastasiya; Dedkova O. A. Olga; Kagadei V. A. Valery; Kamchatnaya O. V. Oksana Valerievna; Lilenko Yu. V. Yury; Yushenko A. Yu. Aleksey (2010, 2010)
Title screen